Entre o palco e a tela : as relações do cinema com o teatro de revista em comédias musicais de Luiz de Barros - Vasconcellos, Evandro Gianasi (Universidade Federal de São Carlos, 2015)
This work aims to study the relationship between the “teatro de revista” (revue) and the musical comedies made by Luiz de Barros. An important name in the history of Brazilian cinema, Luiz de Barros made dozens of films during his long career as a filmmaker. However, he did not dedicate his activities only to cinema, having established also an important career in "teatro de revista" and other stage shows. Based on researches in periodicals and archives, it was made a survey of the many activities of the director. Full of attractions, the musical comedies used elements of mass culture, like popular music and carnival, to attract the audience, bringing also several aspects of the “teatro de revista” and other artistic forms. Through the analysis of the movies Berlim na batucada (Luiz de Barros, 1944) e Caídos do céu (Luiz de Barros, 1946), this research aims to study how the filmmaker articulated characteristic elements of the “teatro de revista” in his films, both in the narrative level and in relation to production, also investigating the casting of theatrical actors and musicians well known to the public. Thus, this work intends to expand a research field of the history of Brazilian cinema that studies the dialogue with other kinds of entertainment.
Keywords: Cinema brasileiro; Luiz de Barros; Comédias musicais; Teatro de revista; Brazilian cinema; Musical comedies; LINGUISTICA, LETRAS E ARTES::ARTES